Komunikasi Pengelola Destinasi Wisata Puncak Pato dengan Pemerintah dalam Upaya Meningkatkan Kunjungan Wisatawan - Firgi Nurdiansyah; Emeraldy Chatra; Sarmiati Sarmiati (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
The increase in tourists which is the main driver of the tourism sector requires the cooperation of all stakeholders consisting of the government and direct cooperation from both the business world and from the private sector. The increase in tourist visits is certainly inseparable from communication activities between actor’s manager of the Puncak Pato tourist area and the government. This communication is important to achieve maximum results in increasing tourist visits to Puncak Pato. The research method used is a phenomenological approach with a constructivism paradigm. The theory used is the Interpretative Phenomenological Analysis theory from Jonathan Smith. Based on the results of the research, it shows that the important concept of communication between managers of the Puncak Pato tourist destination is openness in conveying correct information to the government, an attitude of supporting the government in communication activities and carrying out communication activities with the government in the form of meetings.